Fungal spore transport by omnivorous mycophagous slug in temperate forest. Issue 2 (17th February 2022) - Kitabayashi, Keiko; Kitamura, Shumpei; Tuno, Nobuko
Abstract: Slugs are important consumers of fungal fruiting bodies and expected to carry their spores. In this study, we examined whether slugs ( Meghimatium fruhstorferi ) can act as effective dispersers of spores of basidiomycetes. The microscopic observation confirmed the presence of basidiospores in feces of field‐collected slugs, and the DNA metabarcoding study revealed that Ascomycota and Basidiomycota were major fungal taxa found in the feces. In Basidiomycota, the dominant order was Agaricales followed by Trichosporonales and Hymenochaetales. The laboratory experiments using Tylopilus vinosobrunneus showed that slugs carried a large number of spores in their digestive tracts. It was also observed that Pleurotus, Armillaria, and Gymnopilus spores excreted by slugs had a higher germination capacity than control spores collected from spore prints. The field experiments showed that slugs traveled 10.3 m in 5 h at most by wandering on the ground, litter layers, wood debris, and tree trunks. These results suggest that slugs could carry spores of ectomycorrhizal, saprophytic, and wood‐decaying fungi to appropriate sites for these fungi to establish colonies. Abstract : We examined whether slugs ( Meghimatium fruhstorferi ) can act as effective dispersers of spores of basidiomycetes. Our results suggest that slugs could carry spores of ectomycorrhizal, saprophytic, and wood‐decaying fungi to appropriate sites for these fungi to establish colonies.